Dietary diversity and nutritional adequacy among married Filipino immigrant women: The Filipino Women's Diet and Health Study (FiLWHEL) - Grace P. Abris; Na-Hui Kim; Sherlyn Mae P. Provido; Sangmo Hong; Sung Hoon Yu; Chang Beom Lee; Jung Eun Lee (BMC, 2018)
Abstract Background Migration has an influence on health behavior and food intake. Dietary variety is a key component to high-quality diets because a single food item does not contain a variety of nutrients and may not reflect nutritional adequacy. We aimed to compare the dietary diversity scores (DDS), food variety scores (FVS), and nutrient adequacy levels of married Filipino immigrant women in Korea to those of Korean women. Methods We matched the data of 474 participants aged 20-57 years from the Filipino Women's Diet and Health Study (FiLWHEL) by age category with those of married Korean women randomly selected from the Korea National Health and Nutrition Examination Survey (KNHANES). Dietary information in FiLWHEL and KNHANES were assessed through the 24-hour recall method. We calculated the DDS by summing the number of eleven food groups consumed (DDS 10 g if they consumed at least 10 g/day; DDS all if they consumed any amount) and the FVS by counting the number of food items consumed. For nutrient adequacy, we calculated the probability of adequacy (PA) and intake below the estimated average requirement (EAR). Results Filipino women had a lower DDS and FVS in comparison to Korean women. The means (±SDs) of DDS 10 g, DDS all, and FVS for Filipino women versus Korean women were 6.0 (±1.6) versus 6.8 (±1.5) (p < 0.001), 6.7 (±1.7) versus 7.9 (±1.4) (p < 0.001) and 9.2 (±3.3) versus 14.7 (±4.9) (p < 0.001), respectively. When we compared each food group, the intakes of fish, other seafood, legumes/seeds/nuts, eggs, vegetables, and fruits were lower for Filipino women than for Korean women. The mean probability of adequacy (MPA) of nutrient intake of the nine selected nutrients was lower for Filipino women in comparison to Korean women. The mean (±SD) was 0.55 (±0.28) versus 0.66 (±0.26), respectively. Conclusions Our findings showed that married Filipino immigrant women in Korea had lower dietary variety scores in comparison to Korean women. This was reflected in their nutritional adequacy. Nutrition education focusing on the promotion of eating a variety of foods may be needed for Filipino immigrant women in Korea.